Do Environmental, Social, and Governance (ESG) Factors Matter? Analyzing the Relationships Between Firm Characteristics and ESG Scores - C. N. V. Krishnan; Jiemin Yang; Xiyao Tan (Businesses)
We used three different databases that cover different years from 2006 through 2023 that provide different insights into the associations of firm features with their E, S, and G scores, as well as the composite ESG score. We find that large market capitalization firms are associated with higher ESG and environmental scores as well as with ESG-related strengths. These associations likely stem from the increased scrutiny and expectations from investors, regulators, and the public for large-cap firms. However, we find that changes in ESG scores have no significant associations with changes in basic firm characteristics—market cap, growth options, or profitability. That is, changes in ESG scores over time do not seem to significantly enhance or alter these basic features of a firm.